DAYA TERIMA DAN KANDUNGAN PROTEIN KUE BAGEA SUBSTITUSI TEPUNG IKAN GABUS (OPHIOCEPHALUS STRIATUS) DAN TEPUNG KACANG MERAH (PHASEOLUS VULGARIS L) - Hikmawati Masud; Suriani Rauf; Nurlita Nurlita (Media Gizi Pangan, 2023)
Bagea cake is a typical cake from Palopo City, South Sulawesi. The main ingredient is starch, therefore the nutritional content is mostly carbohydrates. Bagea cake substituted with snakehead fish meal and red bean flour can increase protein content. This study aims to determine the acceptability and protein content of bagea cake substitutes for snakehead fish meal and red bean flour.This type of research is Pre-experimental acceptability test using organoleptic test with a total of 25 panelists. Statistical test using Friedman test. Analysis of protein content using the Kjeldahl method. Data is presented in tabular form accompanied by explanations in narrative form.The results showed that the most preferred acceptability of bagea cake substituted with snakehead fish meal and red bean flour from the aspect of color, aroma, texture, and taste was bagea cake with a concentration of 15%:15%. The results of laboratory tests showed that the protein content in bagea cakes at a concentration of 15%:15% was 6.096 per serving of bagea cakes.It is recommended that in making bagea cake substitutions of snakehead fish meal and red bean flour use a concentration of no more than 15% so that it can be accepted by panelists from the aspect of color, aroma, texture and taste.